Real-World Management and Clinical Outcomes of Stroke Survivors With Atrial Fibrillation: A Population-Based Cohort in Spain - Rodríguez-Bernal, Clara L.; Sanchez-Saez, Francisco; Bejarano-Quisoboni, Daniel; Riera-Arnau, Judit; Sanfélix-Gimeno, Gabriel; Hurtado, Isabel (Frontiers in Pharmacology, 2021)
Objective: Despite the continuous update of clinical guidelines, little is known about the real-world management of patients with atrial fibrillation (AF) who survived a stroke. We aimed to assess patterns of therapeutic management of stroke survivors with AF and clinical outcomes using data from routine practice in a large population-based cohort. Methods: Population-based retrospective cohort study of all patients with AF who survived a stroke, from January 2010 to December 2017 in the Valencia region, Spain (n = 10,986). Treatment strategies and mean time to treatment initiation are described. Temporal trends are shown by management pattern during the study period. Factors associated with each pattern including no treatment -vs. oral anticoagulants (OAC) treatment- were identified using logistic multivariate regression models. Incidence rates of clinical outcomes (mortality, stroke/TIA, GI bleeding, ACS) were also estimated by management pattern. Results: Among stroke survivors with AF, 6% were non-treated, 23% were prescribed antiplatelets (APT), 54% were prescribed OAC and 17% received OAC+APT at discharge. Time to treatment was 8.0 days (CI 7.6-8.4) for APT, 9.86 (CI 9.52-10.19) for OAC and 16.47 (CI 15.86-17.09) for OAC+APT. Regarding temporal trends, management with OAC increased by 20%, with a decrease of 50% for APT during the study period. No treatment and OAC+APT remained relatively stable. The strongest predictor of no treatment and APT treatment was having the same management strategy pre-stroke. Those treated with APT had the highest rates of GI bleeding and recurrent stroke/TIA and untreated patients showed the highest rates of mortality. Conclusions: In this large population-based cohort using real-world data, nearly 30% of AF patients who suffered a stroke were untreated or treated with APT, which overall is not recommended. Treatment was started within 2 weeks as recommended, except for OAC+APT, which was started later. The strong association of APT treatment or non-treatment with the same treatment strategy before stroke occurrence, suggests a strong therapeutic inertia and opposes recommendations. Patients under these two strategies had the highest rates of adverse outcomes. Inadequate prescription pose a great risk on patients with AF and stroke, thus monitoring of their management is necessary and should be setting-specific.